Understanding development of vasculopathy in diabetic microcirculation - role of endothelial prostanoids, prostacyclin and nitric oxide - Rasool, Aida Hanum Ghulam (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2019)
This study aims to elucidate how endothelial dysfunction develops in diabetic • microcirculation. The roles of endothelial derived factors that regulate blood vessel tone and homeostasis: prostacyclin, nitric oxide (NO), endothelium derived hyperpolarizing factors (EDHF) and endothelial prostanoids were studied in streptozotocin induced diabetic rats. The first part of the project involved In-vitro vascular response studies to determine relative contributions of each endothelial NO, EDHF, prostacyclin and prostanoids mediated relaxation /contraction in normal and diabetic vessels. The second part were biochemical studies (western blot and immunohistochemistry) to determine presence and protein expression of the enzymes and receptors involved in synthesis and action of these factors. These experiments were conducted durin'!l early and late phases of diabetes.